ANALISIS PUSAT LISTRIK MINIHIRO (PLTM) STUDI KASUS : SALIDO KECIL PESISIR SELATAN SUMATERA BARAT - Indriani, Rani; Alfith, Alfith (Jurnal Teknologi dan Vokasi, 2024)
In this research, we used a variety of methods that can be applied to the PLTM Salido to address the very low voltage terminal problem of the generator. This is especially true in situations where peak loads occur, which requires these plants to be removed from the system. The power flow analysis is performed using the ETAP Power Station program to simulate the search for operating schemes that can fix the situation. The results of the analysis show that through the injection of reactive power from the generator to the PLN network and the optimization of the governor settings, PLTM Salido can generate more energy by supplying power to PLN networks, even under peak load conditions. This allows PLTM Salido to increase the amount of energy sent from the power plant to the South Coast distribution network. After optimization, the value increased to 14.06 MWh per day from the previous 10.64 MWh By adding one more power plant unit, the energy supply of the PLTM salido could increase to 22 MWh a day.